The Effect of Digital Marketing Implementation through Location Based Advertising on Customerâs Purchase Intention - Wibisurya, Ivan (Bina Nusantara University, 2018)
There were two objectives of the research, those were to find out the effects of Location Based Advertising (LBA) on customerâs attitude and purchase intention. Furthermore, this research sought the enhancement effect of timing in several features on the customerâs attitude toward LBA and purchase intention. The features used were the content appeal, interactivity, control, attitude toward advertising in general, customization, and intrusiveness. This research was a conclusive study with descriptive design. Data collection was done by offline survey with 160 respondents who had ever received LBA in two different conditions. Meanwhile, data analysis was conducted using Structural Equation Modelling (SEM). The research shows several results. First, content appeal, control, and customization have significant and positive effects on attitude toward LBA. Second, attitude toward LBA has significant and positive effect on customerâs purchase intention. Third, timing enhances the positive effect of customization on attitude toward LBA. Last, timing also enhances the positive effect of attitude toward LBA oncustomerâs purchase intention.